A Theoretical Framework for a Pedagogical Model in Lacquer Art Education Focusing on Cultural Knowledge and Artistic Skills - Mingzhu, Ye; Seau, Lee Sze; Ling, Siek Hwee; Ling, Siew Li (Harmonia: Journal of Arts Research and Education, 2025)
As an intangible cultural heritage with more than 8000 years of history, lacquer art now faces threats in sustainability because the sustainability of lacquer art depends on the continuance of human activities around this art form within the community.  In response to the call to action by UNESCO and the Chinese government to sustain lacquer art in the field of education, we identified the problem of developing pedagogical models with a balanced attention to cultural knowledge and artistic skills in lacquer art as the research focus. Methodologically guided by the design phase of a design and development research, this paper discusses a theoretical framework which can ground pedagogical models in lacquer art education. Discussion of results explains and justifies the integration of Culturally Responsive Teaching and Multiliteracies Pedagogy in a theoretical framework that provides design principles and implementation suggestions for pedagogical models targeted at lacquer art, focusing on the Chinese context. It is hoped that future research can adopt or adapt this theoretical framework to design pedagogical interventions that promote cultural knowledge and artistic skills in lacquer art. Specific educational and training programs interested in sustaining intangible cultural heritage through formal and non-formal educational systems can also use this theoretical framework as a point of reference.